Antiproliferative activity of synthetic naphthoquinones related to lapachol. First synthesis of 5-hydroxylapachol - Bonifazi, Evelyn Lucia (2010)
A series of 5-hydroxy-1,4-naphthoquinones analogues was synthesized from juglone (6) and their antiproliferative activity against a representative panel of six human solid tumor cell lines has been investigated. The 2,5-dihydroxy-3-(3-methylbut-2-enyl)naphthalene-1,4-dione (4) and 2,3-dihydro-5-hydroxy-2-(prop-1-en-2-yl)naphtho[2,3-b]furan-4,9-dione (27) were the most potent antiproliferative agents with GI50 values of 0.42-8.1 and 0.80-2.2 μM, respectively. The results provide insight into the correlation between some structural properties of 5-hydroxynaphthoquinones and their antiproliferative activity.